Complete mitochondrial genome of stripped eel catfish (Plotosus lineatus) - Ruan, Zhiqiang (Mitochondrial DNA B Resour, 2016)
The complete mitochondrial genome of stripped eel catfish, Plotosus lineatus, is sequenced in this study. The mitochondrial genome sequence is 16 480 bp in length, with the base composition of 24.7% A, 31.8% T, 27.8% G and 15.7% C. The G + C content is 43.5%. The mitochondria includes 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and one D-loop region. Except for NAD6 gene and eight tRNA genes, all other mitochondrial genes were encoded on the heavy strand. Plotosus lineatus was confirmed to be closely related to P. japonicus (GenBank: KR270437.1), based on our phylogenetic analysis on complete mitochondrial genome sequences of 13 species. Our complete mitogenome data are going to provide the basis for taxonomic and phylogenetic research of catfishes.